Pesantren Strategic Management for Student Achievement in Qur'anic Recitation Competitions - Mustajib; M. Hanif Satria Budi; M. Munif; Khoirotul Izzah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Islamic boarding schools (pesantren) play a strategic role in developing high quality human resources, particularly in fostering students' achievement in the Musabaqah Tilawatil Qur'an (MTQ, Qur'an Recitation Competition), yet most pesantren still manage MTQ coaching incidentally and without systematic structure. This study analyzes in depth the strategic management of Pondok Pesantren Madrasatul Qur'an Tebuireng, Jombang, in developing students' MTQ achievement, covering environmental analysis, strategy formulation, strategy implementation, and strategy evaluation and control. A qualitative case study design was employed, with data collected through in-depth interviews, participant observation, and documentation involving the caretaker, administrators, coaches, and high-achieving students. Data were analyzed using the interactive model of Miles, Huberman, and Saldãna, with validity established through source, technique, and theory triangulation. Findings show that Madrasatul Qur'an applies a systematic and institutionalized value-based strategic management. Environmental analysis is conducted implicitly through leadership understanding, Qur'anic culture, and selective student admission, alongside external dynamics such as national MTQ policy. Strategy formulation is centralistic-normative, with the kiai as the principal strategic-direction setter, supported by annual work meetings. Implementation is carried out through a tiered coaching system integrated with three developmental dimensions: lafdzan, ma'nan, and 'amalan. Strategy evaluation is continuous, conducted through multi-level mechanisms from daily to annual review. This study contributes to the development of a pesantren strategic-management model grounded in religious achievement, relevant to strengthening contextual Islamic educational management theory.